A Review on Indole as a Cardinal Scaffold for Anticancer Drugs Development - Rana, Meenakshi; Ranjan, Rajeev; Sekhar Ghosh, Niladry; Kumar, Dharmendra; Singh, Ranjit (Current Cancer Therapy Reviews, 2024)
Chemotherapy is the mainstay of therapeutic cancer therapy; however, the development of resistance typically makes it less effective. There are continuous efforts by researchers to find novel lead compounds with potent anti-cancer activity. Generally, synthetic or natural heterocyclic compounds have been investigated in detail as a scaffold for cancer therapeutics. Among them, indole, owing to its unique physiochemical and biological properties, provides a promising platform for the development of pharmacophores for drug development against cancer, acting via various mechanisms. Till now, several indole-based derivatives have been identified as anti-cancer agents, which are either being used in clinics or are in various phases of clinical trials, suggesting their importance in anti-cancer drug development. These anti-cancer drugs have been classified into different classes depending on their mechanism of action. For example, histone deacetylase inhibitors (HDAC inhibitors), silent mating type information regulation 2 homolog (SIRT) inhibitors, tubulin inhibitors, proviral insertion site in Moloney murine leukemia virus (Pim) inhibitors, DNA Topoisomerase inhibitors, and kinase inhibitors. In this review, the author's approach is to compile the recent developments on indole-based anti-cancer drugs and provide insight into the respective structureactivity relationships (SARs) of the compounds. We hope the review will provide a thorough understanding to the reader and guide to developing novel and potent indole-based anticancer agents against drug-sensitive and drug-resistant cancer in the future.
Keywords: anti-cancer drug resistance